Dance suite, 4th movement, Maggot - Dubourg, Matthew; Dowdall, William; Adams, David; Dowdall, Lisa; Robinson, Malachy (Atoll, 2015)
The halls of 18th century Dublin resounded with this music, much of it now rediscovered and recorded for the first time.
Airs & dances from Dublin Castle
Spackling Band: William Dowdall (Flute); David Adams (Harpsichord); Malachy Robinson (Viol); Lisa Dowdall (Baroque Viola)
Keywords: Music; Music - 18th century - Dublin; Dubourg, Matthew, 1703-1767